Maternal and neonatal outcomes of vaginal breech delivery for singleton term pregnancies in a carefully selected Cameroonian population: a cohort study. Issue 11 (22nd November 2017) - Dohbit, Julius Sama; Foumane, Pascal; Tochie, Joel Noutakdie; Mamoudou, Fadimatou; Temgoua, Mazou N; Tankeu, Ronni; Aletum, Veronica; Mboudou, Emile
Abstract : Background and objectives: Vaginal breech delivery (VBD) is known to be associated with more perinatal and maternal complications. Very few studies on the subject have been carried out in poor-resource settings. The aim of this study was to determine maternal and neonatal outcomes in carefully selected cases of VBD for singleton term pregnancies in a tertiary centre in Cameroon. Design: A retrospective cohort study. Setting: A tertiary hospital in Yaounde, Cameroon. Participants: Cases of VBD of newborns weighing 2500–3500 g were matched in a ratio of 1:4 to consecutive vaginal cephalic deliveries (VCDs) of newborns weighing 2500–3500 g over a 5-year period. Both groups were matched for maternal age and parity. We excluded cases of multiple gestations, footling breech, clinically inadequate maternal pelvis, preterm delivery, post-term pregnancies, fetal demise prior to the onset of labour, placenta praevia and fetal anomaly incompatible with vaginal delivery. Outcome measures: Neonatal and maternal adverse outcomes of VBD observed till 6 weeks after delivery analysed using Bonferroni correction. Results: Fifty-three (53) VBDs were matched against 212 VCD. Unlike women who had VCD, those who underwent VBD were more likely to have prolonged labour (OR 8.05; 95% CI 3.00 to 11.47; P<0.001), and their newborns were more likely to suffer from birth asphyxia (OR 10.24; 95% CI 4.92 to 21.31; P<0.001). Conclusion: The study infers a strong association between VBD of singleton term pregnancies and maternofetal morbidity when specific protocols are applied. This, however, failed to translate into higher differences in perinatal mortality. This finding does not discount the role of VBD in low-income countries, but we emphasise the need for specific precautions like close monitoring of labour and adequate anticipation for neonatal resuscitation in order to reduce these complications.